Evaluation and proposed revisions of criteria for andosols in the world reference base for soil resources - Shoji, S.; Nanzyo, M.; Dahlgren, R.A.; /Quantin, Paul (1996)
The proposed criteria for andosol classification in the World Reference Base (WRB) of Soil Resources were evaluated using the Tohoku University World Andosol Database (TUWAD). The WRB proposal defines a diagnostic andic horizon comprised of vitr-andic, alu-andic, and sil-andic subtypes, and eight second level soil units. Several notable refinements to the WRB criteria were apparent from evaluation of soil properties from TUWAD and are proposed as revised criteria. Our analysis indicated that the most effective criteria for differentiating the andic horizon were glass content, phosphate retention, oxalate extractable Al and Fe, pyrophosphate-extractable Al, and bulk density. The vitr-andic horizon is distinguished by its low degree of weathering, evident from its low oxalate extractable Al and Fe, low P retention, and high glass content. The ratio of pyrophosphate to oxalate extractable Al is used to separate andic horizons dominated by Al-humus, complexes (alu-andic, Al(p)/Al(o) greater or equal than 0.5), from those dominated by allophanic materials (sil-andic, Al(p)/Al(o) < 0.5). When Al(p) data are not availabe, the Si(o) value of 0.6 could be used as an approximate criteria. We also propose revisions to the nine second level soil units based on the dominant pedogenic processes occurring in andosols : non-crystalline material formation and organic matter accumulation. These soil units are based on the degree of weathering (oxalate extractable Al, Fe, glass content), the dominant weathering agent (organic acids vs. carbonic acid), type (melanic or fulvic) and quantity of organic matter, and high 1.5 MPa water-holding capacity. The revised criteria determined by this study effectively differentiate andosols based on their dominant pedogenic processes, and the relationship or soil properties to productivity and utilization. (Résumé d'auteur)